Junie B. Jones and the stupid smelly bus : the graphic novel / Barbara Park ; - Park, Barbara; Venable, Colleen A. F. (Junie B. Jones graphic novels, 2025)
Junie B. is almost six. Almost six is when you go to kindergarten. And TODAY is Junie B.'s first day of school! Only guess what? Junie B. does NOT want to ride the school bus home. It smells on the bus. Plus also, what if there are meanies on the bus who might pour chocolate milk on your head?! In fact, what if Junie B.'s so scared of the bus that when it's time to go home...she doesn't?!